The role of STEAM-education in teaching mathematics in primary school (MMIT Proceedings, 2024)
The article focuses on the role of STEAM education in mathematics education in elementary grades, and the integration of science, technology, engineering, art, and mathematics is important not only for deep understanding of mathematical concepts, but also for critical thinking, creativity, and problem solving. describes how to help develop skills. The methods of integrating technology and art in teaching mathematics are aimed at making the learning process interactive and stimulating for students. It also emphasized the importance of collaborative learning and social skills developed through joint projects and teamwork.